The Role of Polarizability in Isoelectronic Ions: The Case of Pseudohalides - Mert Acar; Duccio Tatini; Barry W. Ninham; Pierandrea Lo Nostro (Molecules)
Specific ion effects are widespread and have been studied for over a century, yet they remain poorly understood. Terms like “kosmotropes” and “chaotropes” are convenient rules of thumb but the frequent reversal of the Hofmeister series implies their limitations. Polarizability is often used to classify ions, with kosmotropes considered low in polarizability and chaotropes high. However, for polyatomic ions, this framework becomes misleading. The anisotropic nature of polarizability in polyatomic ions plays a decisive role in shaping their behavior. In this work, we study pseudohalides (KOCN, KSCN, and KSeCN) aqueous solutions to explore these effects. We evaluate properties of these anions through experimental measurements of conductivity, density, viscosity, infrared spectra, and polarizability. Our results demonstrate that, even for linear isoelectronic polyatomic ions, the anisotropy of polarizability governs their hydration behavior.